Management of On Table Ruptured of Brachiocephalic Artery Pseudoaneurysm - SHAMSUL BAHRIN, ABDUL HADI; CHANDRAN NADARAJAN; MOHD HAFIZUDDIN HUSIN @ MOHD HUSSIN; NASIBAH MOHAMAD (The Interventionalist Journal, 2023)
Pseudoaneurysms are abnormal outpouching or dilatation of arteries bound only by the tunica adventitia, the outermost layer of the arterial wall. The presence of a pseudoaneurysm is like a ticking bomb that can rupture anytime causing dire consequences for the patient. The brachiocephalic trunk is an uncommon location for such pseudoaneurysms. We present a patient with this uncommon pseudoaneurysm, which ruptured on the table during stent deployment. We will discuss the diagnosis and management plan for this situation as well as the literature review.